Reduction Formula for Primitive of Power of x by Power of a x + b/Decrement of Power of x

From ProofWiki
Jump to navigation Jump to search

Theorem

$\displaystyle \int x^m \left({a x + b}\right)^n \rd x = \frac {x^m \left({a x + b}\right)^{n + 1} } {\left({m + n + 1}\right) a} - \frac {m b} {\left({m + n + 1}\right) a} \int x^{m - 1} \left({a x + b}\right)^n \rd x$


Proof 1

Let $s \in \Z$.

\(\displaystyle v\) \(=\) \(\displaystyle \left({a x + b}\right)^s\)
\((1):\quad\) \(\displaystyle \implies \ \ \) \(\displaystyle \frac {\d v} {\d x}\) \(=\) \(\displaystyle a s \left({a x + b}\right)^{s - 1}\) Power Rule for Derivatives and Derivatives of Function of $a x + b$


Let $u \dfrac {\d v} {\d x} = x^m \left({a x + b}\right)^n$.

Then:

\(\displaystyle u\) \(=\) \(\displaystyle \frac {x^m \left({a x + b}\right)^n} {a s \left({a x + b}\right)^{s - 1} }\) from $(1)$
\(\displaystyle \) \(=\) \(\displaystyle \frac {x^m} {a s} \left({a x + b}\right)^{n - s + 1}\)
\(\displaystyle \implies \ \ \) \(\displaystyle \frac {\d u} {\d x}\) \(=\) \(\displaystyle \frac {m x^{m - 1} } {a s} \left({a x + b}\right)^{n - s + 1} + \frac {x^m} {a s} a \left({n - s + 1}\right) \left({a x + b}\right)^{n - s}\) above rules and Product Rule for Derivatives
\(\displaystyle \) \(=\) \(\displaystyle \frac {x^{m - 1} } {a s} \left({a x + b}\right)^{n - s} \left({m \left({a x + b}\right) + a \left({n - s + 1}\right) x}\right)\) extracting $\dfrac {x^{m - 1} } {a s} \left({a x + b}\right)^{n - s}$ as a factor
\((2):\quad\) \(\displaystyle \) \(=\) \(\displaystyle \frac {x^{m - 1} } {a s} \left({a x + b}\right)^{n - s} \left({m b + a \left({m + n - s + 1}\right) x}\right)\) rearranging


Let $s$ be selected such that $m + n + 1 - s = 0$.

Then $s = m + n + 1$.

Thus $(2)$ after rearrangement becomes:

$\dfrac {\d u} {\d x} = \dfrac {m b x^{m - 1} \left({a x + b}\right)^{n - s} } {\left({m + n + 1}\right) a}$


Then:

\(\displaystyle u v\) \(=\) \(\displaystyle \frac {x^m} {a s} \left({a x + b}\right)^{n - s + 1} \left({a x + b}\right)^s\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {x^m \left({a x + b}\right)^{n + 1} } {\left({m + n + 1}\right) a}\)

and:

\(\displaystyle v \frac {\d u} {\d x}\) \(=\) \(\displaystyle \left({a x + b}\right)^s \frac {m b x^{m - 1} \left({a x + b}\right)^{n - s} } {\left({m + n + 1}\right) a}\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {m b x^{m - 1} \left({a x + b}\right)^n} {\left({m + n + 1}\right) a}\)


Thus by Integration by Parts:

$\displaystyle \int x^m \left({a x + b}\right)^n \rd x = \frac {x^m \left({a x + b}\right)^{n + 1} } {\left({m + n + 1}\right) a} - \frac {m b} {\left({m + n + 1}\right) a} \int x^{m - 1} \left({a x + b}\right)^n \rd x$

$\blacksquare$


Proof 2

From Reduction Formula for Primitive of Power of $a x + b$ by Power of $p x + q$: Decrement of Power:

$\displaystyle \int \paren {a x + b}^m \paren {p x + q}^n \rd x = \frac {\paren {a x + b}^{m + 1} \paren {p x + q}^n} {\paren {m + n + 1} a} - \frac {n \paren {b p - a q} } {\paren {m + n + 1} a} \int \paren {a x + b}^m \paren {p x + q}^{n - 1} \rd x$


Setting $p := 1, q := 0, n := m, m := n$:

\(\displaystyle \int x^m \paren {a x + b}^n \rd x\) \(=\) \(\displaystyle \frac {\paren {a x + b}^{n + 1} \paren {1 x + 0}^m} {\paren {m + n + 1} a} - \frac {m \paren {b 1 - a 0} } {\paren {m + n + 1} a} \int \paren {a x + b}^n \paren {1 x + 0}^{m - 1} \rd x\)
\(\displaystyle \) \(=\) \(\displaystyle \frac {x^m \paren {a x + b}^{n + 1} } {\paren {m + n + 1} a} - \frac {m b} {\paren {m + n + 1} a} \int x^{m - 1} \paren {a x + b}^n \rd x\)

$\blacksquare$


Sources